2019
DOI: 10.1590/1984-70332019v19n1a07
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Eucalyptus grandis families across contrasting environmental conditions

Abstract: The objective was to select productive and stable E. grandis families across contrasting sites in Brazil and Uruguay. Survival and growth of 130 open pollinated families were evaluated three years after planting. Survival ranged from 28 to 89% and mean annual increment from 20.5 to 48.4 m 3 hay-1. Low productivity in one site was attributed to unusually low rainfall and in the other, because of Cylindrocladium leaf disease. Heritability among families and the correlation family by environment were intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Therefore, 32 progenies (25.4 %) can be considered stable and productive, presenting favorable traits for selection and recommendation due to the simple GxE interaction for these progenies. These results are similar to those observed for E. grandis progenies in five experiments established between latitudes 08o 89' to 32°10' in Brazil and Uruguay (Silva et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, 32 progenies (25.4 %) can be considered stable and productive, presenting favorable traits for selection and recommendation due to the simple GxE interaction for these progenies. These results are similar to those observed for E. grandis progenies in five experiments established between latitudes 08o 89' to 32°10' in Brazil and Uruguay (Silva et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…In our case, levels of rainfall lower than the annual average during the study years may have caused the stability in Itamarandiba (2010 = 965 mm; 2011 = 915 mm; annual historic average of 1100 mm) (Inmet, 2017). Similarly, E. grandis families in Itamarandiba, under moderate and prolonged water stress, showed lower productivity levels of the stand and reduced environmental effects on the variation of the phenotype (Silva et al, 2018). Genotype management in a stable environment is more reliable since the genotype ranking will be determined primarily by genotypic effects (Duarte and Vencovsky, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Our results agree with those reported by Silva, et al (2019a;2019b) when evaluating survival and growth in 3-year progeny trials of E. urophylla and E. grandis in different climatic zones of Brazil. These authors reported a survival rate of 51 % to 92 % and an MAI of 19 to 46 m 3 •ha -1 •year -1 for E. urophylla and of 28 to 89 % and 20.5 and 48.4 m 3 • ha -1 •year -1 for E. grandis.…”
Section: Discussionsupporting
confidence: 92%
“…Selection of elite germplasm in intermediate climatic growing conditions allows selection of a suitable germplasm across the diverse range of climatic conditions evaluated (da Silva et al 2019). One approach is characterization of the available germplasm in salt affected environment, which provide an initial germplasm base for breeding salt-tolerant crops.…”
Section: Introductionmentioning
confidence: 99%